TO INVESTIGATE THE RELATIONSHIP BETWEEN NONFINANCIAL BENEFITS TOWARD EMPLOYEE RETENTION - Doris Sin Er, Ng (Universiti Malaysia Sarawak (UNIMAS), 2021)
The purpose of this study s to investigate the relationship between non-financial benefits (wellness program, recognition program, career management, and flexible work schedule) toward employee retention in an IT company, Kuching, Sarawak. The quantitative research methodology used in this research and data were collected using a google form survey questionnaire as the instrument. The analysis of data and information is done using the Statistical Package for Social Science (SPSS). The data were analyzed using descriptive and inferential statistics. Descriptive statistics were reported, followed by hypothesis testing using Pearson correlation and Multiple regression. The findings have shown there is a significant relationship between independent variables (wellness program, recognition program, career management, and flexible work schedule) and employee retention. It was also found that career management is the most dominant factor affecting employee engagement. On the other hand, this study also provides some implications and recommendations for the organization, HR practitioners, and future researchers